Leadership Style Analysis of The Head of The Center for Statistics (BPS) of Tulang Bawang Barat District - Febrian, Valentinus Giovani (Jurnal Ilmiah Sumber Daya Manusia, 2023)
The purpose of this study was to determine the application of the leadership style of the Head of the Central Bureau of Statistics (BPS) of Tulang Bawang Barat Regency. BPS is a Non-Ministerial Government Institution directly responsible to the President, with the vision of "Provider of Quality Statistical Data for Advanced Indonesia". The research method used is qualitative research. The data collection technique used is the interview method and the sample is an employee of BPS Kab. Tulang Bawang Barat. From the research conducted, it can be concluded that of the four existing leadership styles, namely directive, participatory, supportive, and achievement-oriented leadership styles, the most prominent leadership style applied is the directive leadership style. Meanwhile, the least dominant leadership style is an achievement-oriented leadership style.